Say Goodbye and Say Hello: The Transition from Pediatric to Adult Gastroenterology. (1st December 2004) - Pinzon, Jorge L; Jacobson, Kevan; Reiss, John
Abstract : Pediatric and adult gastroenterologists have identified an important issue to be addressed which entails the process of transition of care for youth affected by chronic gastrointestinal disorders. The adolescent years are a time of change and development, and may be significantly affected by conditions such as Crohn's disease or ulcerative colitis. Health care providers need to advocate and provide comprehensive, developmentally appropriate care for youth and families to facilitate the transition from the pediatric to the adult setting. The present article will review important aspects of the transition from the pediatric to the adult care health system.